THE IMPACT OF BASEL III AGREEMENT ON THE ROMANIAN BANKING SYSTEM - Mihaela SUDACEVSCHI (Challenges of the Knowledge Society)
Basel III Agreement is a set of regulations on the banking system, which aims to ensure the system stability, by applying new standards on the capital level and on the liquidity level adequacy and also, on the reduction of banking risk, implied by the financial crisis. Romanian commercial banks will be forced, by the Basel III Agreement implementation, to reduce the risk of capital, using the balance sheet restructuring and by improving the capital quality. The aim of this paper is to analyze the impact of implementing new capital requirements, stipulated by Basel III Agreement, on the Romanian commercial banks, how they will react to the new standards and the decisions they will be able to adopt to respect the standards.